Improving Pancasila and Civic Education Learning Motivation Through Quizzes with Feedback at Senior High School in Poliwali - Anwar Sewang; Mustapa T. (STAI Hubbulwathan Duri, 2022)
This classroom action research aims to increase the learning motivation of Pancasila and civic education subject of Class XII students at a state high school in Polewali by giving quizzes accompanied by feedback. The subjects of this study were all students in that class with the total number of the students were 30 students. The research was conducted in two cycles. The data collection technique was using learning motivation questionnaires and students’ observation sheets. The results showed that giving quizzes accompanied by feedback could increase students’ learning motivation at the high school in Polewali. The beginning of the first cycle resulted in the high category with an average score of 79.33, and the end of the first cycle in the high category was with an average score of 88,93. Meanwhile, the final result of the second cycle was in the very high category with an average of 101.77. This implies that there is a significant improvement of students’ learning motivation after given treatments using quizzes and feedback.